In Tune or Out of Tune: Are Different Instruments and Voice Heard Differently?. (April 2015) - Geringer, John M.; MacLeod, Rebecca B.; Sasanfar, Justine K.
We studied music majors' perception of intonation in accompanied solo performances of trumpet, violin, and voice. We were interested in whether listeners would judge pitch deviations of equal magnitude in the three solo performances as equivalent in intonation. Participants were 150 graduate and undergraduate music majors drawn from two large music schools and included 50 students representing each of the following areas of applied music study: voice, wind instruments, and string instruments. Listeners heard solo trumpet, violin, and soprano performances of Ave Maria (Bach/Gounod) accompanied by piano. Pitch performances of the soloists were altered in four sections of the excerpt and deviated in either the sharp or flat direction within a section by 0, 10, 20, and 30 cents relative to the accompaniment. Listeners judged pitch deviations in the flat direction as more out of tune for the trumpet than equivalent alterations of violin and voice, especially for magnitudes of 20 and 30 cents. In sharp direction changes, violin and trumpet were heard similarly and as more out of tune than the vocal soloist. Additionally, differences in pitch judgments were found between listener groups representing different areas of applied study.